STRATEGI PEMANFAATAN MEDIA SOSIAL DALAM MENINGKATKAN KETERAMPILAN BELAJAR MANDIRI PADA SISWA SEKOLAH DASAR - Laili Etika Rahmawati; Atiqa Sabardila; Minsih; Yunus Sulistyono; Amanda Eka Rismawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify strategies for utilizing social media to improve independent learning skills among elementary school students. The study used a quantitative approach with a survey design involving 100 sixth-grade students in Karanganyar District, Ngawi Regency. The research instrument was a questionnaire with 15 indicators whose validity and reliability have been tested. The results show that the targeted use of social media significantly contributes to improving independent learning skills, particularly in aspects such as consistency in searching for materials, time management, and learning motivation. However, the ability to sort information is still low, so students' digital literacy needs to be strengthened. The conclusion of this study confirms that social media can be an effective tool for encouraging student independent learning when supported by appropriate learning strategies.